Strategy for Islamic Religious Counselors in Minimizing the Occurrence of Divorce in Society - Wasik, Abdul (Nursyam Center, 2024)
This research aims to provide knowledge development regarding the background to the occurrence of divorce and, to understand the duties, functions, and strategies used by Islamic Religious Counselors to minimize the occurrence of divorce in society. The research approach is field research using a qualitative approach. The results show that the strategy is in the form of a Suscatin program, carrying out marriage counseling and counseling before and after the marriage contract. This research implies that the KUA institution is expected to further develop the function of Islamic religious counselors. They should be more active in approaching the society so that the activities carried out run smoothly. The public is expected to actively participate in the activities of the Science Council again through meetings and direct communication without prioritizing social media.